Navigating Emotions, Communication, and Pain During Prehospital Labour: A Mixed-methods Survey With Emergency Ambulance Services - Withanarachchie, Vinuli; Todd, Verity; Dicker, Bridget; Maessen, Sarah E (Springer Science and Business Media LLC, 2025)
Introduction Despite their crucial role in prehospital obstetric emergencies, there is little research exploring emergency medical service (EMS) personnel’s perspectives and attitudes on out-of-hospital births, including balancing the numerous needs of the patient. Our aims were to (1) identify how EMS demographics and professional experience related to their confidence and comfort in treating a patient in labour and (2) explore EMS’ perspectives on managing emotional needs and administering analgesia in a labour and birth setting in New Zealand (NZ). Methods This mixed-methods survey invited frontline clinical personnel from Hato Hone St John – the main EMS provider in NZ – to complete an online survey about unplanned out-of-hospital births. Self-reported confidence attending birth events and administering analgesia to women in labour was compared across participant demographic and professional characteristics. Qualitative content analysis was applied to free-text questions. Results One hundred and forty-seven personnel completed the survey. Only 37% of respondents felt their training had equipped them to confidently manage births, with more experience with birth associated with higher confidence. Men and those who had not given birth were more comfortable providing analgesia to women in labour. Qualitative analysis identified four main categories: (1) Managing their own emotions, (2) Gender differences in views of unplanned births, (3) Managing interpersonal communication with women in labour, the family, and other health professionals, and (4) Views on pain management. The findings indicate that women in labour may be cared for differently depending on EMS clinicians’ personal experiences, communication styles, and attitudes toward pain relief, highlighting the need for these providers to adapt their approach to meet the diverse needs of patients during these high-risk low frequency events. Conclusion EMS personnel navigate a range of emotions and high-risk factors related to their patient and the environment during unplanned pre-hospital births, which may adversely affect their temperament and interpersonal communication. A perception of unclear pain relief guidelines and limited available options can exacerbate challenges. In NZ and overseas, multi-disciplinary training with midwives and integrating maternity and newborn care into postgraduate and ongoing professional development could support EMS personnel to confidently manage these events and improve patient outcomes.
Keywords: 1103 Clinical Sciences; Emergency & Critical Care Medicine; 3202 Clinical sciences; 4203 Health services and systems